Overexpression of PbrNHX2 gene, a Na+/H+ antiporter gene isolated from Pyrus betulaefolia, confers enhanced tolerance to salt stress via modulating ROS levels. (August 2019) - Dong, Huizhen; Wang, Chunmeng; Xing, Caihua; Yang, Tianyuan; Yan, Jinxuan; Gao, Junzhi; Li, Dingli; Wang, Ran; Blumwald, Eduardo; Zhang, Shaoling; Huang, Xiaosan
Highlights: PbrNHX2 expression levels were induced by salt, and dehydration, but was unaffected by cold. Overexpression of PbrNHX2 in tobacco and Pyrus ussuriensis conferred enhanced tolerance to salt tolerance, whereas down-regulation of PbrNHX2 in Pyrus betulaefolia by virus-induced gene silencing (VIGS) resulted in elevated salt sensitivity. The transgenic lines contained lower levels of Na +, higher levels of K +, and higher K/Na ratio, whereas they were changed in an opposite way when PbrNHX2 was silenced. In addition, the transgenic plants accumulated lower levels of reactive oxygen species compared with wild type, accompanied by higher activities of three antioxidant enzymes. Abstract: Intracellular Na + /H + antiporters (NHXs) play important roles in plant tolerance to salt stress. However, plant NHXs functioning in salt tolerance and the underlying physiological mechanisms remain poorly understood. In this report, we report the identification and functional characterization of PbrNHX2 isolated from Pyrus betulaefolia . PbrNHX2 expression levels were induced by salt, and dehydration, but was unaffected by cold. PbrNHX2 was localized in the tonoplast. Overexpression of PbrNHX2 in tobacco and Pyrus ussuriensis conferred enhanced tolerance to salt tolerance, whereas down-regulation of PbrNHX2 in Pyrus betulaefolia by virus-induced gene silencing (VIGS) resulted in elevated salt sensitivity. The transgenic lines contained lower levels of Na +, higher levels of K +, and higher K/Na ratio, whereas they were changed in an opposite way when PbrNHX2 was silenced. In addition, the transgenic plants accumulated lower levels of reactive oxygen species compared with wild type, accompanied by higher activities of three antioxidant enzymes. Taken together, the data demonstrate that PbrNHX2 plays a positive role in salt tolerance and that it holds a great potential for engineering salt tolerance in crops.